2022
DOI: 10.1027/0227-5910/a000812
|View full text |Cite
|
Sign up to set email alerts
|

Nonwillingness to Return to the Emergency Department and Nonattendance of Follow-Up Care Arrangements Following an Initial Suicide-Related Presentation

Abstract: Abstract. Background: For people experiencing a suicidal crisis the emergency department (ED) is often the only option to find help. Aims: The aims of this study were (a) to identify predictors of patients' nonwillingness to return to the ED for help with a future suicidal crisis, and (b) whether nonwillingness to return was associated with follow-up appointment nonattendance. Method: This study utilized baseline data from the RESTORE online survey, and included 911 participants who had presented to an ED for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Further to this, there was an overrepresentation of female participants, as well as limited demographics were collected from participants, and several at-risk demographic groups were not specifically targeted (such as LGBTIQ and Aboriginal and Torres Strait Islander participants), and as such is it difficult to apply this experience across all individuals engaging in emergency suicide crisis care. Nevertheless, these findings are consistent with other Australian studies [2,27,39,40] and it is vital that we honour the lived experience of help-seekers and support people in any service reform and design processes.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Further to this, there was an overrepresentation of female participants, as well as limited demographics were collected from participants, and several at-risk demographic groups were not specifically targeted (such as LGBTIQ and Aboriginal and Torres Strait Islander participants), and as such is it difficult to apply this experience across all individuals engaging in emergency suicide crisis care. Nevertheless, these findings are consistent with other Australian studies [2,27,39,40] and it is vital that we honour the lived experience of help-seekers and support people in any service reform and design processes.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the recruitment method involved participants opting in to take part in an interview, which may have resulted in a biased sample where individuals who had a bad experience may be more likely to want to participate. For instance, some participants had experienced a series of failed attempts to receive help up until their presentation to the ED, which may have negatively coloured their recollections of the visit [2]. As there were only three dyads within the sample, the majority of the sample were unrelated people who attended as either help seeker or support person.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the challenge of delivering high-quality care to people who present to the emergency department following selfharm is not a new problem, and the study by O'Keeffe and colleagues adds to a growing body of literature that documents the challenges experienced by both patients and staff. [5][6][7][8][9] Our own work with young people has shown that emergency departments are often found to be countertherapeutic, with staff appearing to lack both empathy and knowledge when treating young people who selfharm. 5 This is significant as young people (and in particular young females) make up the majority of emergency department presentations for self-harm and rates of presentation in this population appear to have increased during the COVID-19 pandemic.…”
Section: The Wider Literaturementioning
confidence: 99%